IMPLEMENTASI KEGIATAN BACA TULIS AL QUR'AN DALAM MENUMBUHKAN KARAKTER QUR'ANI PADA PESERTA DIDIK SMP MUHAMMADIYAH 4 KEBOMAS GRESIK - Amirudin, Noor; Izhar Nur, Hasby (PENA KREATIF : JURNAL PENDIDIKAN, 2025)
Read Write the Qur'an is an implementation that learns to read the Qur'an correctly and correctly in accordance with the applicable rules. Reading and writing the Qur'an is an activity carried out in educational institutions that is made for students to study the Qur'an properly and correctly, as well as reading by understanding the science of tajweed, makharijul letters and sifatul letters. BTQ activities are one of the religious coaching and planting programs designed so that students can improve their ability to read and write the Qur'an as well as form the character of the Qur'an in students. The research method used is the descriptive qualitative research method, namely the technique of collecting data through observation, interviews and documentation. The results of the study showed that BTQ activities were carried out regularly and structured, personal guidance, and periodic evaluation. This activity has a positive influence on students to form the character of the Qur'ani of students, such as morals, manners, discipline, responsibility, and concern for others. In conclusion, BTQ activities at SMP Muhammadiyah 4 Kebomas have succeeded in becoming an effective means in instilling the value of the Qur'an in the personality of its students.